Entrepreneurial Marketing and Business Performance in System Integrator Start-Ups: A Serial Mediation Analysis Through Technology Customization and Innovation Capability - Pramono, Romy; Kaihatu, Thomas Stefanus; Bernardus, Denny; Mu'min, Halek; Darmanto (International Journal of Accounting and Economics Studies, 2025)
This study identifies the fine-grained linkages between Entrepreneurial Marketing (EM), Technology Customization (TC), Innovation Capability (IC), and Business Performance (BP) of technology-oriented small and medium enterprises (SMEs) with a sequential mediation model. Complementing the resource-based view with dynamic capabilities theory, we propose that entrepreneurial marketing influences business performance both directly and indirectly by way of technology customization and the development of innovation capabilities. Applying partial least squares structural equation modeling to data obtained from SMEs from Indonesia’s technological industry, our findings confirm that entrepreneurial marketing has an extremely high influence on technology customization that significantly enhances innovation capability as well as business performance. Mediation analysis reveals high indirect effects that feature technology customization and innovation capability as crucial mediators for entrepreneurial marketing–performance relationships. However, the extremely high size effects need cautious interpretation because of potential methodological artifacts related to single-source cross-sectional designs. In spite of limitations of the measurement model, such as low convergent validity for innovation capability, the model demonstrates very high predictive power. Our results enhance entrepreneurial marketing literature by spelling out mechanisms of sequential capability development and extend dynamic capabilities theory by empirical validation of interconnected capability relationships. Our study provides practical implications for SMEs driven by technologies that wish to follow integrated capability development strategies by also highlighting that entrepreneurial marketing needs complementary technological and innovation capabilities to pay off. Targeted initiatives, such as staged innovation grants and cross-capability development centers, need to be provided by policies because SMEs need to be strengthened to enhance their competitiveness in fast-evolving competitive situations.